Answer:
g(6) = 71
f(11) = 62
Step-by-step explanation:
Let's solve g(6) first
Plug 6 into x
g(6) = 2(6)^2 - 1
g(6) = 2(36) - 1
g(6) = 72 - 1
g(6) = 71
Now let's solve f(11)
f(11) = 5(11) + 7
f(11) = 55 + 7
f(11) = 62
<em>Thus, out answers are 71 and 62 respectively</em>
Well for the first one you have to subtract 3 on both sides so that would make the equation x > -8 (because a negative subtracting a positive is basically a negative plus negative) and so your equations done. For the second one you divide both ides by -4 so your equation would be x < 4 (the sign would be less then or qual to because you divided by a negative)
Hope I helped you. You didn't even asked any question.
Answer: 1
Step-by-step explanation: There can only be one triangle like that!
-3x-6=2x-1
5x=-5
x=-1
y=-3(-1)-6
y=3-6
y=-3
hope this helps!